The Routledge handbook of mass media ethics - Wilkins, Lee; Christians, Clifford G. (Routledge handbooks., 2020)
"This fully updated second edition of the popular handbook provides an exploration of thinking on media ethics, bringing together the intellectual history of global mass media ethics over the past 40 years, summarising existing research and setting future agenda grounded in philosophy and social science. This second edition offers up-to-date and comprehensive coverage of media ethics, including source ethics, social media, the roots of law in ethics, and documentary film. The wide range of contributors include scholars and former professionals who worked as journalists, public relations professionals, and advertising practitioners. They lay out both a good grounding from which to begin more in-depth and individualized explorations, and extensive bibliographies for each chapter to aid that process. For students and professionals who seek to understand and do the best work possible, this book will provide both insight and direction. Standing apart in its comprehensive coverage, the Handbook is required reading for scholars, graduate students, and researchers in media, mass communication, journalism, ethics, and related areas"--